2016
DOI: 10.1051/shsconf/20162709002
|View full text |Cite
|
Sign up to set email alerts
|

VOT in French as a foreign language: A production and perception study with mono- and multilingual learners (German/Mandarin-Chinese)

Abstract: Abstract. This study addresses the production of Voice Onset Time (VOT) in French as a foreign language (FFL). The learners are young multilingual learners who speak Mandarin Chinese as a heritage language along with German. To determine potential effects of the learners' multilingual background, these multilingual learners were compared to three control groups: (1) monolingual German learners of FFL, (2) monolingual Mandarin Chinese learners of FFL, and (3) native speakers of French (L1). In addition, a perce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(18 citation statements)
references
References 31 publications
1
8
0
2
Order By: Relevance
“…The production of VOT has also received a good deal of attention in the L3 literature (see, for example, Aoki and Nishihara 2013; Bandeira and Zimmer 2012;Beckmann 2012;Dittmers et al 2018;Gabriel et al 2016;Liu 2016;Llama et al 2010;Llama and López-Morelos 2016;Tremblay 2007;Wrembel 2011Wrembel , 2014Wrembel , 2015Wunder 2011). Among the reasons that may have contributed to spur interest on VOT among SLA and TLA researchers are repeated suggestions that it is correlated with degree of foreign accent (Major 2001;Riney and Takagi 1999).…”
Section: L3 Acquisition Of Voice Onset Timementioning
confidence: 99%
See 1 more Smart Citation
“…The production of VOT has also received a good deal of attention in the L3 literature (see, for example, Aoki and Nishihara 2013; Bandeira and Zimmer 2012;Beckmann 2012;Dittmers et al 2018;Gabriel et al 2016;Liu 2016;Llama et al 2010;Llama and López-Morelos 2016;Tremblay 2007;Wrembel 2011Wrembel , 2014Wrembel , 2015Wunder 2011). Among the reasons that may have contributed to spur interest on VOT among SLA and TLA researchers are repeated suggestions that it is correlated with degree of foreign accent (Major 2001;Riney and Takagi 1999).…”
Section: L3 Acquisition Of Voice Onset Timementioning
confidence: 99%
“…We believe that reporting these comparisons allows for the presentation of our findings in a more nuanced way, with a more comprehensive analysis of our participants' behavior in all their known languages. Moreover, it is common practice in similar L3 studies to compare VOT means either to L1 control groups (e.g., Aoki and Nishihara 2013;Beckmann 2012;Gabriel et al 2016) or to L1 reference values from the literature (e.g., Bandeira and Zimmer 2012;Dittmers et al 2018;Wrembel 2011).…”
mentioning
confidence: 99%
“…Statistical analyses showed that, while they had created separate categories for their HL and their ML, their L3 production patterned with the ML. In the same vein, Gabriel et al (2016) found no difference from German monolinguals in the perception and production of L3 French fortis stops in HSs of Mandarin, who theoretically could have transferred shorter values from their HL. However, some evidence for the (co-)occurrence of CLI from the HL also exists, e.g., in HSs with a high degree of metalinguistic awareness (Gabriel & Rusca Ruths, 2015;Özaslan & Gabriel, 2019) or a high proficiency in the HL (Lloyd-Smith et al, 2017).…”
Section: L3 Phonology In Hssmentioning
confidence: 72%
“…Williams (1980) stated, "The apparent development of compromise VOT targets in both perception and production for bilinguals and second-language learners may reflect a true convergence over time of the acoustic phonetic features of the two languages instead of the development of two separate phonetic systems" (p. 213). Subsequently, the term became commonplace in the bilingual speech literature (e.g., Flege and Hillenbrand 1984;Antoniou et al 2010Antoniou et al , 2011Bullock et al 2006;Chang et al 2011;Flege 1991;Eefting 1987b, 1988;Gabriel et al 2016;Jones 2020;Kehoe et al 2004;Kiliç 2018;Kilpatrick 2004;Lein et al 2016;Llama and López-Morelos 2016;López 2012;Morgan 2011;Sundara et al 2006).…”
Section: Background and Motivationmentioning
confidence: 99%